Neuromonitoring During Extracorporeal Membrane Oxygenation: A Systematic Review of the Literature - Bembea, Melania M; Felling, Ryan; Anton, Blair; Salorio, Cynthia F; Johnston, Michael V (Pediatric critical care medicine, 2015)
Neurologic injury remains a significant morbidity and risk factor for mortality in critically ill patients undergoing extracorporeal membrane oxygenation. Our goal was to systematically review the literature on the use of neuromonitoring methods during extracorporeal membrane oxygenation. Electronic searches of PubMed, CINAHL, EMBASE, Web of Science, Cochrane, and Scopus were conducted in March 2014, using a combination of medical subject heading terms and text words to define concepts of extracorporeal life support, neurologic monitoring techniques, evaluation, and outcomes. Studies were selected based on inclusion and exclusion criteria defined a priori. Two authors reviewed all citations independently. A standardized data extraction form was used to construct evidence tables by neuromonitoring method. Evidence was graded using the Oxford Evidence-Based Medicine scoring system. Of 3,459 unique citations, 39 studies met the inclusion criteria. Study designs were retrospective observational cohort studies (n = 20), prospective observational studies (n = 17), case-control studies (n = 2), and no interventional studies. Most studies evaluated newborns (n = 30). Extracorporeal membrane oxygenation neuromonitoring methods included neuroimaging (head ultrasound) (n = 12); intermittent, conventional, multichannel electroencephalography (n = 5); 1- to 2-channel amplitude-integrated electroencephalography (n = 2); Doppler ultrasound (n = 7); cerebral oximetry (n = 6); plasma brain injury biomarkers (n = 4); and other (n = 3). All evidence was graded 2B-4, with the majority of studies graded 3B (20/39 studies) and 4 (10/39 studies). Due to the heterogeneity of the studies included, aggregate analysis was not possible. Data supporting the use and effectiveness of current neuromonitoring methods are limited. Most studies have modest sample sizes, are observational in nature, and include patient populations that are of different ages and pathologies, with very limited data for pediatric and adult ages. Well-designed studies with adequate power and standardized short- and long-term outcomes are needed to develop guidelines for neuromonitoring and ultimately neuroprotection in patients on extracorporeal membrane oxygenation.